Evolution of sodium-glucose co-transporter 2 inhibitors from a glucose-lowering drug to a pivotal therapeutic agent for cardio-renal-metabolic syndrome - Akiyama, Hiroki; Nishimura, Akihiro; Morita, Naru; Yajima, Toshitaka (Frontiers in Endocrinology, 2023)
Cardio-renal-metabolic (CRM) syndrome, which involves type 2 diabetes mellitus (T2DM), chronic kidney disease (CKD), and heart failure (HF), is a serious healthcare issue globally, with high morbidity and mortality. The disorders that comprise CRM syndrome are independent can mutually affect and accelerate the exacerbation of each other, thereby substantially increasing the risk of mortality and impairing quality of life. To manage CRM syndrome by preventing vicious interactions among individual disorders, a holistic treatment approach that can simultaneously address multiple disorders underpinning CRM syndrome is of great importance. Sodium-glucose co-transporter 2 inhibitors (SGLT2i) lower blood glucose levels by inhibiting glucose reabsorption in the renal proximal tubule and were first indicated for the treatment of T2DM. Several cardiovascular outcome trials have demonstrated that SGLT2i not only lower blood glucose but also reduce the risk of hospitalization for HF and worsening renal function in patients with T2DM. Results have also suggested that the observed cardiorenal benefits of SGLT2i may be independent of their blood glucose-lowering effects. Several randomized controlled trials subsequently assessed the efficacy and safety of SGLT2i in patients without T2DM, and revealed considerable benefits of SGLT2i treatment against HF and CKD, regardless of the presence of T2DM. Thus, SGLT2i have become an essential therapeutic option to prevent the onset, slow the progression, and improve the prognosis of CRM syndrome. This review assesses the evolution of SGLT2i from a glucose-lowering drug to a therapeutic agent for CRM syndrome by evaluating epoch-making clinical studies, including randomized control trials and real-world studies.